Non-Formal Education and Its Influence in Overcoming Adolescent's Moral Damage Through The Youth Group of Al-Ikhwan Mosque - Amir Faqihuddin Assafary; Husrah Husrah (P3I Luwu Raya, 2020)
This study discusses non-formal education and its influence in overcoming the moral damage of adolescents through the youth group at the Al-Ikhwan Mosque Tampumia Radda Belopa, Luwu Regency. It aims to determine the moral improvement of adolescents in participating in activities carried out through the Al-Ikhwan Mosque Youth Group. In this study, the authors used data collection methods through observation, interviews and offering a number of questions to the people of the Tampumia Radda village. The data collected were analyzed qualitatively and quantitatively. The results of this study indicate that through non-formal education, naughty teenagers can become teenagers who are aware, obedient to their parents, and become responsible teenagers. Based on the questionnaire distributed to respondents, 93% of the community stated that the presence of the mosque youth group gave peace to Tampumia Radda, Luwu Regency, even according to calculations the average number of parents who agreed was 81%, disagreed 15.2% while only 7, 8 % Disagree.